# Math - Functions

posted by
**Anonymous** on
.

I know the following equation is definitely NOT EVEN, BUT I DO NOT KNOW WHY IT'S NOT ODD!. . .

PLEASE. . .EXPLAIN THOROUGHLY!. . .

y = 2(x - 1)^2 + 3

f(-x) = 2(-x - 1)^2 + 3

f(-x) does not equal f(x), therefore, not even. . .

-f(x) = -[2(x + 1)^2 + 3]

-f(x) = -2(-x - 1)^2 - 3

-f(x) does not equal f(x), therefore, not odd ----- BUT WHY? I DON'T SEE THIS!!!!!. . .

Isn't the equation y = 2(x - 1)^2 + 3 opposite of y = -2(-x + 1)^2 - 3?????????